2006
DOI: 10.3201/eid1708.060291
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Resistance in Klebsiella pneumoniae Not Detected by Automated Susceptibility Testing

Abstract: Detecting β-lactamase-mediated carbapenem resistance among Klebsiella pneumoniae isolates and other Enterobacteriaceae is an emerging problem. In this study, 15 bla KPC -positive Klebsiella pneumoniae that showed discrepant results for imipenem and meropenem from 4 New York City hospitals were characterized by isoelectric focusing; broth microdilution (BMD); disk diffusion (DD); and MicroScan, Phoenix, Sensititre, VITEK, and VITEK 2 automated systems. All 15 isolates were either intermediate or resistant to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
106
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 10 publications
0
106
1
3
Order By: Relevance
“…MICs derived by the Vitek 2 system were usually comparably low for imipenem and meropenem, whereas testing with microbroth dilution revealed higher MICs. This problem has been reported previously 33 . However, the Vitek 2 system is widely used in Chinese laboratories, and if included in the testing panel such as AST-GN13, ertapenem may serve as an indicator for the detection of IMP carbapenemase.…”
mentioning
confidence: 55%
“…MICs derived by the Vitek 2 system were usually comparably low for imipenem and meropenem, whereas testing with microbroth dilution revealed higher MICs. This problem has been reported previously 33 . However, the Vitek 2 system is widely used in Chinese laboratories, and if included in the testing panel such as AST-GN13, ertapenem may serve as an indicator for the detection of IMP carbapenemase.…”
mentioning
confidence: 55%
“…Some authors [38,39] have shown that some isolates with MICs for imipenem/meropenem within the susceptibility range can possess KPC enzymes, and then the detection of the carbapenemases may be difficult. In this study, all isolates were resistant to carbapenems, showing a MIC90 of 64 μg/mL for meropenem/imipenem and a MIC90 >128 μg/mL for ertapenem.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of carbapenems by KPCs has been demonstrated in vitro (1,21,22); however, multiple studies have reported variability in susceptibility testing of KPC-producing clinical isolates (2,3,13,22). Although variation in KPC enzyme production could contribute to the variability seen during susceptibility testing, it is difficult to assess the influence of the KPC ␤-lactamase on susceptibility testing using clinical isolates which may harbor multiple ␤-lactamases and may have alterations in outer membrane proteins (4,7,9,10,21,24). Therefore, we used cloning and transformation to create a panel of four different genera of Gram-negative bacteria that expressed the bla KPC gene without the influence of other resistance mechanisms.…”
mentioning
confidence: 99%